DETERMINAÇÃO DOS EFEITOS DA DESSECAÇÃO ANTECIPADA EM CANOLA SOBRE O RENDIMENTO DE GRÃOS E SEUS COMPONENTES - VALENTINI, ANA P. F.; FIORIN, CARLOS A.; ZAMBONATO, FELIPE; GAVIRAGHI, FERNANDO; MARTINS, JOÃO A. K.; SILVA, JOSÉ A. G. D.; WAGNER, JULIANO F.; MOTTA, MARCELO; CARBONERA, ROBERTO; MEDEIROS, VOLNEI D. (Salão do Conhecimento, 2013)
Resumo